Tourism Object Valuation Determined Based on Environmental Services Using Travel Cost Method at Tegal City Alam Indah Beach - Doni Triono; Adro Mediantoro (International Journal of Social Service and Research, 2022)
Alam Indah Beach is located in a strategic urban coastal area so it has a very high potential to be used as a tourist attraction. This study aims to determine descriptively the analysis of the socio-economic characteristics of visitors and to know quantitatively the economic value of the Alam Indah Beach Tourism Object and the relationship between several variables that affect the number of visits from the object. This research is a quantitative study with primary and secondary data collection through library research and field studies using interviews, observation, and questionnaires. The results of the study reveal that the total cost variable has the most significant influence on the number of tourist visits, reaching 80.27% and resulting in a total consumer surplus of IDR. 130.355.024, willingness to pay of IDR. 136,497, and an economic valuation of IDR. 35,508,314,810. Major economic benefits from tourism activities in Alam Indah beach brings socio economic improvement of the local community. The result of economic value of beach tourism object could be a reference for managers and local governments to balance between beach as a preservation with additional income for local governments and societies.